Evaluation of the knowledge, attitudes and behaviors of pre-school teachers on oral and dental health in the city center of Trabzon - Ezgi Baltacı; Özgül Baygın; Tamer Tüzüner; Fatih Mehmet Korkmaz (Istanbul University, 2019)
Purpose Educators can also contribute to the prevention of early childhood caries (ECC) by educating children about oral diseases and hygiene practices. The aim of this study was to assess the knowledge, attitudes, and behaviors of pre-school teachers concerning oral and dental health in Trabzon. Subjects and methods The study was carried out with 226 pre-school teachers in the city center using a self-administered questionnaire to evaluate their knowledge, attitudes, and behaviors concerning the oral and dental health of children. Results Only 29.8% of the respondents had a prior dental education. Although 83% of the teachers said that regular visits to the dentist were effective for caries prevention, only 13.2% said that they made regular visits to a dentist. Approximately 65.8% of the teachers agreed that fluoride strengthens tooth enamel and 35.1% of the teachers said that there were oral health activities in their schools. Additionally, 74.6% of teachers said that they would participate in dental education about children's oral health in the future. Conclusion Preventive dental health program could be implemented including the proper behaviors related to the importance and treatability of primary teeth, first tooth cleaning, dental visits, the use of fluoride toothpaste, and oral hygiene into the preschool teachers' undergraduate education programs in the future. This program should be repeated at certain intervals for the prevention of ECC.